Groundwater recharge sites and pollution sources in the wine-producing Guadalupe Valley (Mexico): Restrictions and mixing prior to transfer of reclaimed water from the US-México border - Daesslé, L. W.; Andrade-Tafoya, P. D.; Lafarga-Moreno, J.; Mahlknecht, J.; van Geldern, Robert; Beramendi-Orosco, L. E.; Barth, Johannes (Science of the Total Environment, 2020)
Rapid depletion of aquifers in semiarid and arid regions threatens water security. This holds true especially in emerging countries where insufficient knowledge about aquifer systems precludes the implementation of advanced management measures, such as managed aquifer recharge. This study deals with the generation of baseline knowledge for the assessment of aquifers in arid and semiarid regions where artificial recharge with reclaimed water gains increasing impetus. The Guadalupe aquifer in Baja California provides water to 57% of the Mexican wine industry. Recent plans foresee a partial replenishment of its depleted groundwater reserves by transferring treated waste water from the Mexico-USA border for irrigation. The aquifer demonstrated to have a rapid response by rising the water table of about +20 m in relation to natural recharge under an intense rainfall period of 236 mm. Two predominant recharge sources were identified based on a geochemical multi-tracer approach: (a) water of modern age (<5 yr, >1.8 TU) and mixed water of recent-submodern age (3H 0.8–1.8 TU), and (b) sub-modern waters that were recharged before 1952 (3H < 0.5 TU). Water of the first type originate in the main Guadalupe stream, which has a more depleted average δ18O isotope value (−7.8‰) than average local rainwater (−2.0‰). The stream water initially has a Na-HCO3 composition and recharges the entire Calafia zone and most groundwater along the riverbed across the valley. Water of the second type is mostly derived from hill-slope groundwater that has a stable isotope composition of mixed local rainwater and a Na[sbnd]Cl composition. High total dissolved solids >2 g l−1 together with enriched NO3 − and Se concentrations characterize groundwater in the downstream the Porvenir zone. The geochemical age of this older, hill-slope groundwater suggests that its replenishment takes at least several decades when it becomes exhausted.
CRIS-Team Scopus Importer:2020-01-28
Keywords: Aquifer; Groundwater recharge; Mexico; Return flows; Stable isotopes; Tritium; Wastewater